Effects of apartheid legacy on South African judo: a systematic review - Hlasho, T. S.; Mathunjwa, M. L.; Shaw, B.; Shaw, I. (American Journal of Sports Science, 2024)
Presently, the sport of Judo in South Africa (JSA) has substantially failed to grow and gain publicity nationally and internationally due to the low number of judokas representing the country. Concurrently, each country has unique motivators and barriers to engagement in sports. On that note, during the period of apartheid (1948-1994), South African (SA) government enacted Group Areas Act to ensure that whites and blacks did not stay together leading in segregated sport trainings and match facilities, which culminated in skewed career opportunities in sport. Therefore, the purpose of this review was to reflect on how SA apartheid system impacted the development of judo in SA. An in-depth search strategy was conducted from inception to April 2023, which involved PubMed, SportDiscuss, Google Scholar and Web of Science. This study`s findings indicate that the system of apartheid disrupted sport in South Africa particularly with sport opportunities and resources being reserved for white athletes. Further, this study`s results indicate that JSA was segregated based on race, location, and social standing. In conclusion, sport participation and access to resources by all should be created to ensure equity and justice for all athletes and coaching staff. This leads to an all-inclusive integrated sports development plan which will increase sport involvement by the citizens. In this effect, JSA introduced free and development registration for athletes who cannot afford to pay fees and this gesture has helped poor athletes access judo.